New model end milling parameters based on screening test on aluminum alloy (AA6041) - Sudianto, Agus; Jamaludin, Zamberi; Rahman, A. A. Abdul (KOLECER Scientific Journal of Mechanical Engineering, 2025)
The manufacturing industry aims to achieve high productivity and quality products in the production process. Many factors have direct and indirect influences on realizing the two production objectives. Among them are part geometry, process conditions, and the environment. The correct and best process selection must be made on the right machine with the optimum parameters in the machining process application. This paper presents the results of screening studies performed on a milling process involving milling parameters such as the cut speed, feeding speed, depth of cut, cutting width, and flute. The screening results aim to decide the optimal milling parameters for the process. The screening process was performed on a CNC Milling HAAS machine using aluminum alloy (AA6041) with end mill cutter HPMT 303 1000 070 and HPMT S42 1000 072 of AL SE STD Ø10 utilized in dry cutting conditions. The results of this screening process were then analyzed through ANOVA with the help of Minitab 19.0 using the Taguchi method. In this work, three sets of machining parameters obtained from the screening process were then applied in experimental work, whereby the surface finish outcomes become the basis for determining the quality of the process based on the maximum surface roughness value.